The Prevalence of Autoantibodies in Complex Regional Pain Syndrome Type I - Maaike Dirckx; Marco W. J. Schreurs; Marissa de Mos; Dirk L. Stronks; Frank J. P. M. Huygen (Hindawi Limited, 2015)
Autoimmunity has been suggested as one of the pathophysiologic mechanisms that may underlie complex regional pain syndrome (CRPS). Screening for antinuclear antibodies (ANA) is one of the diagnostic tests, which is usually performed if a person is suspected to have a systemic autoimmune disease. Antineuronal antibodies are autoantibodies directed against antigens in the central and/or peripheral nervous system. The aim of this study was to compare the prevalence of these antibodies in CRPS patients with the normal values of those antibodies in the healthy population. Twenty seven (33%) of the 82 CRPS patients of whom serum was available showed a positive ANA test. This prevalence is significantly higher than in the general population. Six patients (7.3%) showed a positive result for typical antineuronal antibodies. This proportion, however, does not deviate from that in the general population. Our findings suggest that autoantibodies may be associated with the pathophysiology of CRPS, at least in a subset of patients. Further research is needed into defining this subset and into the role of autoantibodies in the pathogenesis of CRPS.